Finite element simulation of arrays of hollow sphere structures: Finite‐Elemente‐Simulation von Hohlkugelstrukturen in verschiedenen Anordnungen. Issue 4 (May 2015) - Amani, Y.; Öchsner, A.
Abstract : The numerical simulation of a repetitive model of a cellular metal is developed for fundamental investigation of the elastic behaviour of hollow sphere structures. Syntactic and partial morphologies of simple cubic configurations of hollow sphere structures are prescribed under boundary conditions corresponding to unit cells and periodic hollow sphere lattices. The obtained results are plotted as diagrams of Young's modulus versus relative density and allow to explain the behaviour of hollow sphere structures independent of their basic elastic properties.